G420(P) Prevention of congenital syphilis: What are the strengths and challenges in a tertiary maternity hospital?. (27th April 2016) - Johnston, NF; Macken, WL; Cunningham, O; Connell, MO
Abstract : Introduction: Syphilis infection is increasing in Ireland. Women with previous or active infection risk transmission to their child with potentially devastating consequences. An evidence-based syphilis management algorithm is used nationally to aid decision making with regard to investigation and treatment for such infants (Figure 1 ). We aimed to review demographic trends and audit management of syphilis exposed infants in a large tertiary maternity hospital. Methods: A retrospective chart audit identified all infants born to mothers with acute or previous syphilis infection between January 2012 and June 2015. We captured maternal demographic and serological information, birth characteristics, risk assessment at birth, diagnostic testing, treatment and adequacy of follow-up. Results: 32 mothers were included. 87.5% of mothers were non-Irish and many did not speak English (Figure 2 ). Of 35 pregnancies, 28 (80%) involved previous infection with adequate treatment. 7 (20%) were new or inadequately treated infections. 94% of babies were correctly assigned to their risk category. 10 (9.4%) infants received a single dose of IM benzathine penicillin and 1 had 14 days of intravenous penicillin. 4 infants (11.4%) were overtreated. In these cases, the algorithm was absent from the infant's medical notes and the decision to treat was made out-of-hours by a junior doctor. All infants had appropriate follow up. None were undertreated (Figure 3 ). Conclusions/recommendations: Our centre is highly adherent to an evidence-based syphilis management algorithm. The presence of a copy of the algorithm in the medical chart provides a useful visual reference to aid decision making. Where algorithms are not available, the infant is at risk of being investigated or treated inappropriately. Communication difficulties are a major challenge in the prevention of congenital syphilis. Non-English speaking mothers may have poor disease knowledge and may be at increased risk of being loss to follow up. We recommend Education sessions for doctors with regard to use of the algorithm Placement of a copy of the algorithm that identifies risk category in the infant chart Promotion of translator services and native language information leaflets for non-English speaking mothers